Academic attraction programs: The cases of the Catedras Patrimoniales Subprogram in Mexico and the Prometeo Program in Ecuador - Pedone, Claudia; Izquierdo, Isabel (Education Policy Analysis Archives, 2018)
The study focuses on the experiences of foreign academics who participated in two programs for attracting qualified personnel, one in Mexico, “Subprograma de Cátedras Patrimoniales” (1991-2002), and another in Ecuador, the “Programa Prometeo” (2008-2014). We analyzed in a general way the context, the implementation and the institutional ways for diffusion of the programs within the framework of the governments, and policies of both countries. The study identified these programs as innovative policies; however it was also noted that the interest of the group of academics in benefiting from these programs was to alleviate their economic crisis and the lack of investment in science and technology in their countries of origin rather than the response to a demand from Mexico and Ecuador in pursuit of the internationalization of higher education.